2022
DOI: 10.1038/s42255-022-00605-w
|View full text |Cite
|
Sign up to set email alerts
|

TFEB induces mitochondrial itaconate synthesis to suppress bacterial growth in macrophages

Abstract: Successful elimination of bacteria in phagocytes occurs in the phago-lysosomal system, but also depends on mitochondrial pathways. Yet, how these two organelle systems communicate is largely unknown. Here we identify the lysosomal biogenesis factor transcription factor EB (TFEB) as regulator for phago-lysosome-mitochondria crosstalk in macrophages. By combining cellular imaging and metabolic profiling, we find that TFEB activation, in response to bacterial stimuli, promotes the transcription of aconitate decar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 73 publications
1
40
0
Order By: Relevance
“…4A, B). This result was not expected and may reflect a change in phosphorylation sites without a net change in number of phosphorylated residues of TFEB and/or heterogeneous infection rates that is not resolvable by a population-based assay such as Western blotting (Puertollano et al ., 2018), or may suggest that TFEB is regulated through another mechanism such as the recently discovered itaconate modification of TFEB (Zhang et al ., 2022; Schuster et al ., 2022). Interestingly, the levels of total TFEB normalized to actin were reduced in macrophages infected for 4 h with late-log-phase Salmonella , indicating that under specific conditions, Salmonella can repress TFEB expression or promote its degradation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4A, B). This result was not expected and may reflect a change in phosphorylation sites without a net change in number of phosphorylated residues of TFEB and/or heterogeneous infection rates that is not resolvable by a population-based assay such as Western blotting (Puertollano et al ., 2018), or may suggest that TFEB is regulated through another mechanism such as the recently discovered itaconate modification of TFEB (Zhang et al ., 2022; Schuster et al ., 2022). Interestingly, the levels of total TFEB normalized to actin were reduced in macrophages infected for 4 h with late-log-phase Salmonella , indicating that under specific conditions, Salmonella can repress TFEB expression or promote its degradation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, host macrophages engage a TFEB-Irg1-itaconate signalling axis in response to Salmonella , whereby TFEB promotes Irg1-driven itaconate production. Itaconate then alkylates and promotes TFEB nuclear translocation, which helps restrict Salmonella survival (Zhang et al ., 2022; Schuster et al ., 2022). As described, the activation of TFEB is macrophage-driven.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the AcpM’s role in the suppression of antimicrobial responses against Mtb infection seems to be associated with the inhibition of TFEB, but not directly related to the suppression of autophagy. In addition, a recent study revealed that TFEB activation is required for the induction of mitochondrial itaconate synthesis to control intracellular bacterial growth ( 44 , 45 ), suggesting the critical function of TFEB in terms of antimicrobial defense in macrophages. Future studies will clarify whether AcpM is involved in the regulation of immunometabolic remodeling in macrophages to further affect TFEB-induced antimicrobial responses during Mtb infection.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Schuster et al . reported TFEB as a transcription factor for IRG expression, which is critical for removing intravacuolar pathogen Salmonella Enterica Serovar Typhimurium ( 85 ). Physiologically relevant carbon source for itaconate synthesis has also been explored in a comprehensive tracing analysis showing glucose and glutamine as major fuels for itaconate production ( 27 ).…”
Section: Itaconatementioning
confidence: 99%